Hybrid frictional contact particles-in elements - Dhia, Hachmi Ben; Zarroug, Malek (European Journal of Computational Mechanics, 2002)
By analyzing functional, geometrical and numerical integration aspects, hybrid frictional contact particles-in-elements are derived from the continuous hybrid formulation of 3D large transformation frictional contact problems given in [BEN 99] [BEN 00a]. The suggested approach is illustrated by some academic and industrial contact tests.